2017
DOI: 10.1074/jbc.m117.804997
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of the Haemophilus influenzae peptidoglycan synthase activator LpoA suggest multiple conformations in solution

Abstract: In many Gram-negative bacteria, the peptidoglycan synthase PBP1A requires the outer membrane lipoprotein LpoA for constructing a functional peptidoglycan required for bacterial viability. Previously, we have shown that the C-terminal domain of LpoA (LpoA) has a highly conserved, putative substrate-binding cleft between two α/β lobes. Here, we report a 2.0 Å resolution crystal structure of the LpoA N-terminal domain. Two subdomains contain tetratricopeptide-like motifs that form a concave groove, but their rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The TPR domains are the most likely candidates for the portion of Pa LpoP that directly interfaces with Pa PBP1b, and this region probably does so by binding the UB2H domain like Ec LpoB. Consistent with this possibility, TPR domains are broadly distributed in biology to mediate protein-protein interactions (15) and are found in many regulators of cell-wall biogenesis, including LpoA (5)(6)(7)18), NlpI (19,20), and CpoB (21). Interestingly, the periplasmic protein CpoB in E. coli is thought to use its TPR domain to associate with Ec PBP1b via its UB2H domain during cell division to coordinate Ec PBP1b activity with that of the Tol-Pal system during cell division (21).…”
Section: Discussionmentioning
confidence: 86%
“…The TPR domains are the most likely candidates for the portion of Pa LpoP that directly interfaces with Pa PBP1b, and this region probably does so by binding the UB2H domain like Ec LpoB. Consistent with this possibility, TPR domains are broadly distributed in biology to mediate protein-protein interactions (15) and are found in many regulators of cell-wall biogenesis, including LpoA (5)(6)(7)18), NlpI (19,20), and CpoB (21). Interestingly, the periplasmic protein CpoB in E. coli is thought to use its TPR domain to associate with Ec PBP1b via its UB2H domain during cell division to coordinate Ec PBP1b activity with that of the Tol-Pal system during cell division (21).…”
Section: Discussionmentioning
confidence: 86%
“…The predicted sequence of the mature EcLpoA N-domain protein was serine followed by residues 31-252 of EcLpoA (formula weight 25 154). The cloning, expression and purification of residues 33-253 of the HiLpoA N domain were identical to the procedures described previously (Sathiyamoorthy et al, 2017). The gene fragment with NcoI and SalI restriction sites corresponding to residues 33-253 of HiLpoA was amplified using PCR from genomic DNA isolated from the H. influenzae Rd strain (ATCC catalog No.…”
Section: Macromolecule Productionmentioning
confidence: 99%
“…LpoA is composed of two domains: a primarily helical amino-terminal (N) domain and a carboxyl-terminal domain involved in interactions with PBP1A. Analyses of multiple crystal structures of full-length LpoA from Haemophilus influenzae (HiLpoA), together with small-angle X-ray scattering results, suggested that LpoA is a flexible molecule that is capable of extending through gaps or holes in PG in order to interact with the inner-membranebound PBP1A (Sathiyamoorthy et al, 2017). Although the interdomain linker is responsible for much of the flexibility of the molecule, twists and bends of up to 5 have been observed within the N domain and are likely to affect the overall length of the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations